Pif1, RPA, and FEN1 modulate the ability of DNA polymerase δ to overcome protein barriers during DNA synthesis - Sparks, Melanie A. (J Biol Chem, 2020)
Successful DNA replication requires carefully regulated mechanisms to overcome numerous obstacles that naturally occur throughout chromosomal DNA. Scattered across the genome are tightly bound proteins, such as transcription factors and nucleosomes, that are necessary for cell function, but that also have the potential to impede timely DNA replication. Using biochemically reconstituted systems, we show that two transcription factors, yeast Reb1 and Tbf1, and a tightly positioned nucleosome, are strong blocks to the strand displacement DNA synthesis activity of DNA polymerase δ. Although the block imparted by Tbf1 can be overcome by the DNA-binding activity of the single-stranded DNA-binding protein RPA, efficient DNA replication through either a Reb1 or a nucleosome block occurs only in the presence of the 5'-3' DNA helicase Pif1. The Pif1-dependent stimulation of DNA synthesis across strong protein barriers may be beneficial during break-induced replication where barriers are expected to pose a problem to efficient DNA bubble migration. However, in the context of lagging strand DNA synthesis, the efficient disruption of a nucleosome barrier by Pif1 could lead to the futile re-replication of newly synthetized DNA. In the presence of FEN1 endonuclease, the major driver of nick translation during lagging strand replication, Pif1-dependent stimulation of DNA synthesis through a nucleosome or Reb1 barrier is prevented. By cleaving the short 5' tails generated during strand displacement, FEN1 eliminates the entry point for Pif1. We propose that this activity would protect the cell from potential DNA re-replication caused by unwarranted Pif1 interference during lagging strand replication.